Pelaksanaan Metode Tikrar Dalam Tahfiz Al- Qur’an Kelas 7 di Pondok Pesantren Ti Tarusan Kamang, Nagari Kamang Mudiak - Erni Sasmitha; Salmi Wati; Arman Husni; Pendi Hasibuan (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
The reason for the author to raise this scientific work in the form of a thesis is because the writer found that in implementing the pledge method in tahfiz Al-Qur'an there were still obstacles faced by the teacher in implementing the pledge method. The problem that the author examines is how to implement the pledge method in tahfiz Al-Qur'an and the obstacles faced by teachers and students when using the pledge method at the TI Tarusan Kamang Islamic Boarding School. And this study aims to determine the implementation and constraints in using the tikrar method in tahfiz Al-Qur'an. This study uses a type of field research (field research) with a descriptive qualitative research type, which describes a phenomenon that occurs in accordance with existing data in the field. This study used two informants, namely the key informant was the tahfiz teacher at the Tarusan Kamang Islamic Boarding School, and the supporting informant was the students of the Tarusan Kamang Islamic Boarding School. Data collection techniques that researchers use are observation, interviews and documentation. Based on the results of the research conducted, the researchers found that at the Tarusan Kamang Islamic Boarding School not all students had Al-Qur'an tikrar and did not use the columns provided in the Al-Qur'an tikrar to mark the limits of memorization, muraja'ah and recitations.